Motivasi dan Strategi Belajar Siswa dalam Pendidikan Pembelajaran Berbasis Masalah dan Collaborative Learning di Fakultas Kedokteran Gigi Universitas Hasanuddin - Ayub Irmadani Anwar; Yayi Suryo Prabandari; Ova Emilia (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2013)
Background: Education providers in many ways short of expectations. Education strategy is essential in teaching and learning activities. Student who has motivation and learning strategies tends to devote all their ability to get the optimal learning results according to the expected goals. Understanding student motivation and learning strategies will help institution to facilitate students for their study success. This study aimed of determine differences in student motivation and learning strategies at Faculty of Dentistry, University of Hasanuddin among students with collaborative learning and problem-based learning educational strategies.Method: This was quantitative research with observational analytic cross-sectional study design. The subjects were all students of class 2007 and 2008 data were collected using Motivated Strategies for Learning Questionnaire (MSLQ). Descriptive analysis and Mann-Whitney test were used to analysis the data.Results: The subjects consisted of 84 students of class 2007 and 79 students of class 2008. The mean score of learning motivation and learning strategy were higher among students with PBL than students with collaborative learning. There we are significant differences in learning strategies with different education strategies except in organization (p=0,369) and anxiety (p=0.058).Conclusion: There are differences in the learning motivation and learning strategies in students with collaborative learning and problem based learning education strategies, except in organization and anxiety component. Learning motivation and learning strategies in problem based learning students are higher than collaborative learning students.